Svetlana (Nominated play, excerpt) - Terziyska, Kalina (Sledva : NBU Journal of Humanities and Arts, 2020)
Svetlana is a theatre collage of soulscapes of a few women born in Bulgaria, Russia and the USA before the fall of the Berlin Wall. Memories from the past alternate with letters, fantasies, and conflicts. The story of Svetlana Alliluyeva, Stalin’s daughter, is in the center of the play. Parallel to it is the story of Ada, born in the 1970s Bulgaria. Mainly in the form of monologues, the two women speak on the topic of money, truth, family, and the imprint of history on every person’s life.